2020
DOI: 10.1177/0391560320960003
|View full text |Cite
|
Sign up to set email alerts
|

Urine and serum glycosaminoglycan levels in the diagnosis of urological diseases and conditions: A narrative review of the literature

Abstract: Glycosaminoglycans (GAGs) are sulfated, negatively charged polysaccharides produced in almost every cell of the human body. As GAGs are extracellularly localized, the changes in body fluids such as blood and urine may reflect pathological changes in the urinary system as observed in other pathologies. In this review, we determined the potential of urinary and/or serum GAG levels as a marker for kidney and urothelial system diseases. We performed a search in the PubMed, MEDLINE, and ScienceDirect databases unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…In general, urinary biomarker levels are frequently studied in various disease as they can be measured both noninvasively and easily. GAGs, a polysaccharide molecule produced in every cell in the human body, exist in two main structures as sulfated and non-sulfated (16,17). Non-sulfated GAG contains hyaluronic acid, while sulfated GAGs include chondroitin sulfate, dermatan sulfate, keratan sulfate, heparan sulfate, and heparin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, urinary biomarker levels are frequently studied in various disease as they can be measured both noninvasively and easily. GAGs, a polysaccharide molecule produced in every cell in the human body, exist in two main structures as sulfated and non-sulfated (16,17). Non-sulfated GAG contains hyaluronic acid, while sulfated GAGs include chondroitin sulfate, dermatan sulfate, keratan sulfate, heparan sulfate, and heparin.…”
Section: Discussionmentioning
confidence: 99%
“…Non-sulfated GAG contains hyaluronic acid, while sulfated GAGs include chondroitin sulfate, dermatan sulfate, keratan sulfate, heparan sulfate, and heparin. GAGs are in the structure of the basal lamina of the urethra, and damage to the GAG layer can affect the basal functions of the urothelium (17,18). This process may result in the bladder surface being exposed to microcrystals, proteins, calcium, toxic metabolic products, and carcinogens of the urine (19).…”
Section: Discussionmentioning
confidence: 99%
“…Due to metabolic abnormalities, crystals such as uric acid and calcium oxalate (CaOx) accumulate in the renal pelvis or calyces of patients' urine, resulting in stone formation. It has been found that the type and content of GAGs in urine may be closely related to the formation process of renal calculi [253][254][255]. Some earlier studies demonstrated that CS and HS inhibited the formation of kidney stones, while HA promoted stone formation and growth [256][257][258].…”
Section: Gags In Other Diseasesmentioning
confidence: 99%
“…The bladder urothelium provides a protective barrier against the penetration of toxic agents, urine, and bacteria. The glycosaminoglycan (GAG) layer consists of a thick mucus layer of glycoproteins and proteoglycans on the surface of the urothelial cells [ 13 ]. The main components of this superficial layer are chondroitin sulfate (CS) and hyaluronic acid (HA).…”
Section: Introductionmentioning
confidence: 99%